2001
DOI: 10.3186/jjphytopath.67.33
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and control of ripe rot symptoms on persimmon fruit.

Abstract: rot disease on mature fruit of persimmon (Diospyros kaki) occurred in several areas in Gifu Prefecture where persimmon is extensively produced. The disease was characterized by rotting from the fruit apex or base. From the results of fungal isolation and tests of their pathogenicity, the rotting was caused by two species of the fungal genus Pestalotiopsis. One was identified as Pestalotiopsis longiseta (Spegazzini) Dai et Kobayashi and the other as P. foedans (Saccardo et Ellis) Steyaert, on the basis of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a study by McQuilken and Hopkins (2004), it was found that Pestalotiopsis isolates were non-specific and affected other plant species causing the typical dark brown spots. Likewise, Taguchi et al (2001) suggested that Pestalotiopsis spp. isolates are not host specific.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by McQuilken and Hopkins (2004), it was found that Pestalotiopsis isolates were non-specific and affected other plant species causing the typical dark brown spots. Likewise, Taguchi et al (2001) suggested that Pestalotiopsis spp. isolates are not host specific.…”
Section: Discussionmentioning
confidence: 99%
“…P. theae also has been reported to cause leaf blight of Japanese persimmon (Nojima 1928). Recently, P. foedans (Saccardo & Ellis) Steyaert was reported to be the pathogen of ripe rot of persimmon fruits (Taguchi et al 2001). In this study, P. longiseta was predominant on Japanese persimmon in many orchards in Tottori Prefecture, and P. acaciae, P. crassiuscula, and P. glandicola were isolated in some orchards (unpublished data).…”
mentioning
confidence: 81%
“…Previous inoculation experiments and host range studies have indicated that isolates of Pestalotiopsis spp. generally are not host-specific, but they can infect a wide range of plants (Taguchi et al 2001). It is thought that vegetation around the persimmon orchard may greatly influence the predominant species of Pestalotiopsis that causes various diseases on persimmon trees.…”
mentioning
confidence: 99%